Radiative heat transfer of second grade nanofluid flow past a porous flat surface: a single-phase mathematical model - Jamshed, Wasim; Nisar, Kottakkaran Sooppy; Gowda, R J Punith; Kumar, R Naveen; Prasannakumara, B C (Physica scripta, 2021)
The current study explores the nanofluid flow and heat transfer properties by exposing it to a slippery surface. The effect of radiation, heat source, porous medium, and viscous dissipation are also comprised in this analysis. The arising partial differential equations from boundary layer equations of the second grade nanoliquid model are reformed into non-linear ordinary differential equations using suitable transformations. The solution of these equations is then cracked by means of shooting numerical scheme. In this investigation, we used two different types of nanoparticles, Alumina (Al 2 O 3 ) and Copper (Cu), along with a non-Newtonian Engine Oil (EO) as based liquid. The valuable finding of this scrutiny is that the comparative heat transference rate of Cu-EO second grade nanofluids gradually more increases as compared to Al 2 O 3 -EO nanofluids. Results reveal that, the parameters have a massive effect on the heat transfer very close to the wall and are slightly away from the wall. The escalation in nanoparticle volume fraction and second grade parameters declines the velocity profile.